Central Control of Feeding Behavior by the Secretin, PACAP, and Glucagon Family of Peptides - Sekar, Revathi; Wang, Lei; Chow, Billy Kwok Chong (Frontiers in Endocrinology, 2017)
Constituting a group of structurally related brain-gut peptides, secretin, PACAP and glucagon family of peptide hormones exert their functions via interactions with the class B1 G protein-coupled receptors (GPCRs). In recent years, the roles of these peptides in neuroendocrine control of feeding behavior have been a specific area of research focus for development of potential therapeutic drug targets to combat obesity and metabolic disorders. As a result, some members in the family and their analogues have already been utilized as therapeutic agents in clinical application. This review aims to provide an overview of the current understanding on the important role of secretin, PACAP and glucagon family of peptides in neuroendocrine control of feeding behavior.